Women Entrepreneurs in Botswana: Reducing Poverty and Creating Employment - Sibanda, Khulekani (Journal of Business and Management Review, 2024)
Research Aims: The objective of this study is to examine the influence of women entrepreneurship on the generation of employment opportunities and the alleviation of poverty in Botswana. The study seeks to provide a thorough comprehension of how businesses headed by women contribute to economic transformation. Design/methodology/approach: The study used a mixed-method approach, integrating both qualitative and quantitative data. The qualitative data was obtained by conducting surveys and interviews with women entrepreneurs in Botswana, supplemented by secondary data from official and non-governmental reports. The quantitative data were analysed using the statistical software SPSS to obtain comprehensive results. Research Findings: Women-owned businesses in Botswana make a substantial impact on job creation. Many of these businesses employ a workforce ranging from 5 to 20 workers, while some larger organisations provide employment to over 50 people. These businesses play a crucial role in reducing poverty by actively participating in community development projects, such as constructing schools and clinics. As a result, they directly enhance the welfare of local communities. The qualitative findings highlight the diverse and complex contributions of women entrepreneurs in promoting community development and reducing poverty. These findings emphasise their commitment to social accountability, economic sustainability, and resilience in the face of challenges. Theoretical Contribution/Originality: This study offers novel perspectives on the distinct contributions made by women entrepreneurs in Botswana, emphasising their dual impact on both economic progress and societal transformation. The study also highlights the primary challenges encountered by women-owned small and medium enterprises (SMEs), such as restricted financial resources, socio-cultural hindrances, and insufficient governmental assistance. It emphasises the significance of overcoming these issues in order to maximise the positive influence of women-owned SMEs on employment generation and alleviation of poverty